PENDAFTARAN PERALIHAN HAK GUNA BANGUNAN DI ATAS HAK PENGELOLAAN SETELAH PENGALIHAN TUGAS DARI BAGIAN UMUM SETDA KOTA MEDAN KEPADA BAGIAN PERLENGKAPAN DAN ASET SETDA KOTA MEDAN (STUDI PADA PEMERINTAH DAERAH KOTA MEDAN - DIANA ANGGRENI (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Muhd. Yamin2. Syafruddin Kalo3. Syahril Sofyan The Handover of Tasks in the General Department of Setda, Medan, on the regulation of Building Right above the Right of Management which causes obstacles in giving permit/approval of title transfer in the Logistics and Asset Department because the Right of Management of Medan Municipality is the Regional Government-Owned Property of Medan and its operation cannot be transferred to other party. It can only be extended within 5 years which is similar to the Right of Lease, Building Rights on the Right of Management can be transferred by referring to the agreement for using the land form the holder of the Right of Management provided that its Building Right is in effect, and the legal consequence of delaying giving the approval to the holder of the Right of Management will cause certificate deficiency and legal uncertainty toward the buyer.Keywords: Transfer, Building Rights, the Right of Management